Factors Affecting Auditor Independence: An Approach Based on Structural Equation Modeling - sotudeh, Reza (Business, Marketing, and Finance Open, 2025)
This study aimed to investigate the factors affecting auditor independence. The statistical population included auditors active in public and private organizations, stock exchange member companies, and regulatory bodies related to the auditing profession, from which a sample of 384 individuals was selected using stratified random sampling. The data collection tool was a standard questionnaire whose validity and reliability were confirmed using Cronbach's alpha and factor analysis. The results showed that auditor characteristics, economic factors, legal and regulatory factors, factors related to the work environment and the client, and the client's organizational characteristics have a positive and significant effect on auditor independence. Among these factors, the client's organizational characteristics had the greatest effect. The findings emphasize the importance of strengthening legal supervision, improving financial structures, promoting the professional characteristics of auditors, and reducing management pressures to maintain auditor independence. These results can help improve policy-making and the design of educational and supervisory programs in the auditing profession.